Micro-mechanical homogenisation of three-leaf masonry walls under compression. (15th October 2021) - Drougkas, Anastasios; Sarhosis, Vasilis
Highlights: Multi-scale micro-mechanics accurately predict the compressive strength of masonry. Leaf interaction in multi-leaf walls is modelled by simple analytical expressions. Unit dimensions & secondary elements strongly affect the compressive strength. Abstract: Three-leaf masonry panels are typically composed of external leaves of irregularly bonded units and a rouble infill. The complexity of the response of these structures to mechanical loading arises from: a) the interaction of the leaves and b) the irregularity of the bond pattern of the outer leaves. This complexity makes analytical and computational modelling of these structures difficult and costly, respectively. This paper proposes a computational approach for the calculation of the mechanical properties of the three-leaf masonry from the properties of its constituent materials and its geometry. Using micro-mechanical analysis approaches applied in composite materials and accounting for the interaction of the leaves through a simple analytical approach, the homogenised elastic stiffness and strength of a representative volume element of three-leaf masonry can be calculated with very low computational cost. The analysis method is validated against experimental results from the literature. It is found that the proposed model provides accurate results for a relatively wide range of case studies. These results are expanded upon through a sensitivity study, highlighting the most important material and geometric parameters influencing the predicted compressive strength of three-leaf masonry walls.